Karakteristik Penggusuran di Indonesia: Pentingnya Intervensi HAM Sebelum, Sewaktu, dan Setelah Penggusuran - Mochamad Felani Budi Hartanto; Dian Andi Nur Aziz; Agus Suntoro (Jurnal HAM, 2023)
Development and spatial planning policies, especially physical infrastructure, are closely tied to the changes in land use. When these policies intersect with public living spaces, there is a possibility that they are leading to eviction. Although driven by public interest considerations"”such as infrastructure development, post-disaster relocation and reconstruction, river flow normalization--evictions in Indonesia often coincide with conflicts, violence, lack of information, and inadequate compensation. These eviction practices are closely associated with alleged human rights violations. This article aims to critically examine the normative aspects of eviction policies and practices in Indonesia from a human rights perspective. It also raises the idea of human rights intervention in eviction policies and practices, aiming at establishing an ideal balance between spatial planning needs and human rights protection for displaced communities. By juxtaposing eviction policies and practices in Indonesia with human rights instruments related to evictions, this kind of intervention is necessary in within three time frames of eviction, namely before, during, and after evictions. Within these temporalities, the government should consider all alternatives outside evictions, provide clear information including eviction procedures, ensure protection for affected communities, and ensure reparative efforts for impacted communities.